Analisis Perbandingan Yield to Maturity, Harga, dan Durasi Antara Obligasi Korporasi dengan Obligasi Pemerintah Indonesia - Egita Riyanti Supangadi; Sri Ulina Kaban; Amalya, Diska; Siti Munawaroh; Fauzan Adhipramana; Humairah, Reni (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The bond market in Indonesia continues to develop and become one of the investment instruments of interest, both by institutional and individual investors. This study aims to compare the characteristics of government bonds and corporate bonds based on several factors such as Yield to Maturity (YTM), bond prices, and duration (Macaulay and Modified Duration). The method used is comparative quantitative analysis with secondary data obtained from the website of Kustodian Sentral Efek Indonesia (KSEI). The results of the study indicate that government bonds have a lower risk with a YTM of 6%, a market price of IDR990,000.00, a macaulay duration of 1,903  years, and a modified duration of 1,82 years. In contrast, corporate bonds offer higher returns with a YTM of 12.14%, a market price of IDR980,000.00, a Macaulay duration of 1,847 years, and a modified duration of 1,77 years. Thus, this study is expected to provide insight for investors in adjusting investment choices based on risk profiles and financial goals.